The Implementation of the Accounting Standard (Psak 405) For Mudharabah Financing: A Study on BPD DIY Syariah - Octaviani, Irma; Fithria, Annisa (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2024)
Indonesia, as a predominantly Muslim country with 87.1% of its population adhering to Islam, has seen significant growth in Islamic financial institutions, including banks and cooperatives. These institutions adhere to Sharia principles, replacing interest-based systems with profit-sharing mechanisms. This study focuses on BPD DIY Syariah, a Sharia Business Unit of BPD DIY, and examines its implementation of mudharabah financing accounting in accordance with PSAK 405. Using qualitative methods, including interviews and document analysis, the research highlights the alignment of BPD DIY Syariah's practices with PSAK 405 standards, covering recognition, measurement, presentation, and disclosure. The findings indicate conformity in accounting treatment but also reveal challenges in transparency due to integration with the parent bank's financial reporting. The study underscores the importance of consistent adherence to Sharia accounting standards to foster public trust and enhance professionalism within the Islamic banking sector. Recommendations for future research include expanding the scope to additional Islamic banks for broader insights.